1999
DOI: 10.1152/jappl.1999.87.6.2168
|View full text |Cite
|
Sign up to set email alerts
|

Influences of thigh cuffs on the cardiovascular system during 7-day head-down bed rest

Abstract: Thigh cuffs, presently named "bracelets," consist of two straps fixed to the upper part of each thigh, applying a pressure of 30 mmHg. The objective was to evaluate the cardiac, arterial, and venous changes in a group of subjects in head-down tilt (HDT) for 7 days by using thigh cuffs during the daytime, and in a control group not using cuffs. The cardiovascular parameters were measured by echography and Doppler. Seven days in HDT reduced stroke volume in both groups (-10%; P < 0.05). Lower limb vascular resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 28 publications
2
43
4
Order By: Relevance
“…(2004), who reported an unaltered tibial and gastrocnemial vein diameter after 90 days of bed rest. These findings do not correspond with the previous results of a decrease in cross-sectional area of the popliteal and femoral vein (Arbeille et al 1999(Arbeille et al , 2001) and the common result of a decreased venous volume variation after bed rest (Bleeker et al , 2005aChrist et al 2001;Louisy et al 1997). The arterial vascular system also presented diameter reductions after deconditioning (Bleeker et al 2005a, b;De Groot et al 2006), but these changes over time were remarkably larger than previously shown in the venous vascular system.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…(2004), who reported an unaltered tibial and gastrocnemial vein diameter after 90 days of bed rest. These findings do not correspond with the previous results of a decrease in cross-sectional area of the popliteal and femoral vein (Arbeille et al 1999(Arbeille et al , 2001) and the common result of a decreased venous volume variation after bed rest (Bleeker et al , 2005aChrist et al 2001;Louisy et al 1997). The arterial vascular system also presented diameter reductions after deconditioning (Bleeker et al 2005a, b;De Groot et al 2006), but these changes over time were remarkably larger than previously shown in the venous vascular system.…”
Section: Discussioncontrasting
confidence: 54%
“…Both venous capacitance and compliance are major determinants in the vital functions of the venous system, and a numerous amount of studies have been performed to specify their role in orthostatic intolerance after bed rest and space flight in humans. To study the effect of physical deconditioning on the venous vascular system, several human deconditioning models have been used, such as leg immobilisation (Bleeker et al 2005a), space flight (Arbeille et al 2001;Fomina and Kotovskaia 2005;Watenpaugh et al 2001), bed rest (Arbeille et al 1999(Arbeille et al , 2001Belin de Chantemele et al 2004;Bleeker et al 2005b;Bonde-Petersen et al 1994;Buckey et al 1992;Christ et al 2001;Convertino et al 1989;Louisy et al 1997;Melchior and Fortney 1993;Xiao et al 2005) and spinal-cord injury (Frieden et al 1987;Hopman et al 1994;Wecht et al 2000). Sparse data on venous diameter show a reduction in cross-sectional area of femoral venous diameter after bed rest (Arbeille et al 1999(Arbeille et al , 2001), but no change in tibial and gastrocnemial venous diameter (Belin de Chantemele et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…We set out to determine the blood pressure, heart rate (HR), and baroreflex response to standing, before and after spaceflight, using frequency domain-and a (novel) high-resolution time domain BRS computation (21). We conducted a preflight stand test with and without venous thigh cuffs to induce venous "trapping" of blood in the lower limbs (1,15). We hypothesized that if the tachycardia and hypotension after spaceflight are indeed related to central hypovolemia, reductions in central blood volume could mimic postspaceflight response to standing.…”
mentioning
confidence: 99%
“…Thus, during KAATSU, arterial baroreceptors as well as cardiopulmonary baroreceptors were unloaded (Furlan et al 2001;Brown et al 2003), which mimicked orthostatic stress. During actual space flight, the Russian physicians have already used a unique method for a countermeasure, called ''bracelets'' to reduce edema and venous stasis in the cephalic region by pooling blood in the vascular and extravascular compartments of the legs (Lindgren et al 1998;Arbeille et al 1999;Millet et al 2000). This method applies a pressure of *30 mmHg, proposing that the degree of venous pooling induced by the bracelets is much lower than that observed in KAATSU, where the cuff pressure of 100-250 mmHg is used to restrict muscle blood flow and increase muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…An elastic thigh cuff, called ''bracelets'', has been reported to be an effective passive countermeasure for reducing edema and venous stasis in the cephalic region by pooling blood in the vascular and extravascular compartments of the legs, easing the stress of zero gravity (Lindgren et al 1998;Arbeille et al 1999;Millet et al 2000). However, the effectiveness of bracelets to prevent cardiovascular deconditioning is incomplete, providing only partial compensation for the cardiovascular changes (Herault et al 2000).…”
Section: Introductionmentioning
confidence: 99%